Nomograph of self-compacting concrete mix design incorporating coal bottom ash as partial replacement of fine aggregates - Hamzah, A. F. (Medwell Journals, 2016)
In this study, a waste mineral by-product produced from coal-fired power plant known as Coal Bottom Ash (CBA) is composed as admixture and used as a substitute materials to the fine aggregates in Self-Compacting Concrete (SCC) with replacement ratio range from 0-30% by volume. A brief account of experimental investigations is presented based on the physical and mechanical properties were determined by consuming water cement ratios (W/C) of 0.35, 0.40 and 0.45. The data obtained shown are significant in relationship of CBA percentage between W/C ratios, compressive strength, tensile strength and flexural strength. The results were combined into a graph form to develop a primary mix design nomograph. It is shown that the developed nomograph is able to assist in designing mix proportion based on the essential parameter required.